Fiscal union in Europe? Redistributive and stabilizing effects of a European tax‐benefit system and fiscal equalization mechanism. Issue 75 (15th July 2013) - Bargain, Olivier; Dolls, Mathias; Fuest, Clemens; Neumann, Dirk; Peichl, Andreas; Pestel, Nico; Siegloch, Sebastian
Summary: The current debt crisis has given rise to a debate concerning deeper fiscal integration in Europe. The view is widespread that moving towards a 'fiscal union' would have stabilizing effects in case of macroeconomic shocks. We study the economic effects of introducing two elements of a fiscal union: an EU‐wide tax and transfer system and a fiscal equalization mechanism. Using the European tax‐benefit calculator EUROMOD, we exploit representative household micro data from 11 eurozone countries to simulate these policy reforms and study their effects on the income distribution and automatic stabilizers. We find that replacing one third of the national tax‐benefit systems with a European system would lead to significant redistributive effects both within and across countries. These effects depend on income levels and the structures of existing national systems. The EU system would particularly improve fiscal stabilization in credit constrained countries absorbing 10–15% of a macroeconomic income shock. Introducing a fiscal equalization mechanism would redistribute revenues from high to low income countries. However, the stabilization properties of this system are ambiguous. The results suggest that it might be necessary for Europe to explore alternative ways of improving macroeconomic stability without redistributing income ex ante. — Olivier Bargain, Mathias Dolls, Clemens Fuest, Dirk Neumann, Andreas Peichl, Nico Pestel and Sebastian Siegloch